2011
DOI: 10.3354/meps09035
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and phylogeography of Atlantic oyster species: evolutionary history, limited genetic connectivity and isolation by distance

Abstract: The phylogenetic relationships between naturally occurring Atlantic Crassostrea oyster species were inferred through analyses of mitochondrial (cytochrome oxidase subunit I and 16S) and nuclear (second internal transcribed spacer) sequences. We also scored 15 allozyme loci on 422 oysters to study population structuring of C. rhizophorae and C. brasiliana along 9000 km of the Western Atlantic coastline. Despite morphological similarities, C. virginica was genetically more closely related to C. rhizophorae than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 65 publications
6
45
0
4
Order By: Relevance
“…Broodstock and larvae were sampled for identification with molecular biology techniques as described by Melo et al (2010) and Lazoski et al (2011). The molecular analyzes were performed at Laboratório de Biodiversidade Molecular, at Universidade Federal do Rio de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Broodstock and larvae were sampled for identification with molecular biology techniques as described by Melo et al (2010) and Lazoski et al (2011). The molecular analyzes were performed at Laboratório de Biodiversidade Molecular, at Universidade Federal do Rio de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
“…The nursery and grow-out lanterns were cleaned twice and once a month, respectively, to remove mud and fouling organisms. After five months of culture in the grow-out from Florianópolis, state of Santa Catarina, South of Brazil, to the state of Pará, in the North (Melo et al, 2010;Lazoski et al, 2011), but with a discontinuity in the coast of Bahia, Northeastern Brazil, possibly due to inefficient sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens of the oyster Crassostrea gasar (= C. brasiliana) used in this study was previously identified to the species level using molecular techniques (Lazoski et al, 2011). Oysters measuring between 43 and 70 mm in height (Galtsoff, 1964) were stocked in suspended longline lanterns.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Molecular studies (Varela et al 2007;Melo et al 2010a;Melo et al 2010b;Lazoski et al 2011) from the Atlantic coast of South America indicated the existence of four species of Crassostrea distributed in natural beds, including two native species Crassostrea gasar (Adanson, 1757; sin. Crassostrea brasiliana Lamarck 1819) and Crassostrea rhizophorae (Guilding 1828), and two non-native Indo-Pacific oysters, Crassostrea gigas (Thunberg, 1793) and Crassostrea sp (Gardunho et al 2012).…”
mentioning
confidence: 99%